CONSTRUÇÃO DE CÂMARA BIOCLIMÁTICA DE BAIXO CUSTO PARA ESTUDOS DE AMBIÊNCIA TÉRMICA NO BRASIL - Trevisan, Livia Yu Iwamura; Tamura, Cintia Akemi; Ribeiro, Daniele Abe; Gomes, Beatriz de Lyra Monteiro; Drach, Patricia Regina Chaves; Hara, Massayuki Mário; Krüger, Eduardo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article presents the construction of Cost-effective Bioclimatic Building Chamber (CBBC), an innovative Brazilian facility dedicated to the investigation of environmental comfort, bioclimatic architecture, and building performance. The CBBC project took into account the current Bioclimatic Zoning and the Technical Regulations for Energy Efficiency Labelling of Commercial Buildings. It was implemented in Bioclimatic Zone 1, a temperate wet maritime climate (Köppenand an experimental unit which can undergo modifications as to allow diverse experiments. The biggest challenge during construction was the low budget available, as discussed in this article. Construction phases and current status are shown as a project portfolio.